(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
E-retailing has changed the retail environment in India. Consumer's attitude towards shopping has been changed with the introduction of internet. Due to Internet world has become a small village. The e-retailing website is the primary door of the online store that interacts between the e-retailer and consumers. The electronic retailing (e-retailing, internet retailing etc.) is the way of selling goods using electronic media, in particular, the internet. Providing the customers more comfort and convenience to purchase the goods. In India, the use of mobile phones, internet adoption, and the availability of low cost data plans have contributed in the growth of e-retailing. The close of physical stores in COVID-19 epidemic has also increase the growth of eretailing in India. As a result, customers start shopping through online. However, the expansion of e-retailing has also brought many difficulties, such as the effect on conventional brick-and-mortar merchants, worries about data privacy, and the requirement for a strong logistics and supply chain infrastructure. In this research paper the authors propose to explore the profile of e-retailing customer’s and to investigate conceptually the challenges and the avenues involved in e- Retailing.